Transnational, translocal, transcultural: some remarks on the relations between Hindu-Balinese and ethnic Chinese in Bali - Gottowik, Volker (Sojourn, 2010)
In the course of the spatial turn in the social sciences, new terms and categories have emerged. This paper applies categories like translocal and transcultural to the way the Hindu-Balinese perceive themselves in order to bring out certain principles of their ethos and world view. This world view is symbolically expressed through a pair of black and white figures, Barong Landung, who are venerated as sacred by many Hindu-Balinese and perceived as representing their first ancestors or Kawitan. This multiethnic couple reminds the Hindu-Balinese that their origin as a people lies outside their island, that their religion derives from India, and that parts of their culture once came from China. Against the background to this rather global self-understanding of a local culture, the paper asks how the Hindu-Balinese define their relations with the ethnic Chinese in Bali. (Sojourn/GIGA)